Comparison Analysis of Content of Shopee And Tokopedia E-Commerce Marketing Management Strategies Through Instagram Social Media - Ramadhan, Alfian (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2023)
Instragram social media provides business opportunities and sells a variety of products at more affordable prices than general stores. Researchers want to see a comparison of promotion strategies through Instagram content from the two e-commerce companies and provide knowledge about the promotional activities carried out, and researchers want to find out how the two e-commerce can lead the e-commerce market in Indonesia. This research will analyze the Business to Customer (B2C) E-Commerce marketing management strategy using content analysis (content analysis). This research is a qualitative descriptive research. Data was collected using library research methods and field research using observation techniques. The results of the study show that on the product indicator, Shopee displays product-related uploads while Tokopedia does not. On the people indicator, both e-commerce displays uploads regarding the people category with the most frequency of uploads compared to other categories. In this people indicator too, Shopee has more uploads related to the people indicator than Tokopedia. On the price indicator , Shopee displays uploads while on Tokopedia it doesn't . On the promotion indicator, which is divided into 4 (advertising, direct marketing, sales promotion, publicity), Shopee does not display uploads related to publicity. Meanwhile, Tokopedia does not display uploads related to advertising and publicity. To refer to the promotion strategy, namely in the Promotions, Shoppe and Tokopedia sections most often display the Sales Promotion category.It's a shame they don't display Corporate Social Responsibility .